The effect of pre-pregnancy hair dye exposure on infant birth weight: a nested case-control study - Chao Jiang; Qingzhi Hou; Yaling Huang; Juan Ye; Xiaolian Qin; Yu Zhang; Wen Meng; Qiuyan Wang; Yonghua Jiang; Haiying Zhang; Mujun Li; Zengnan Mo; et al. (BMC, 2018)
Abstract Background Limited evidences were reported about the risk of pre-pregnancy hair dye use or irregular menstruation with abnormal birth weight during pregnancy, and their joint effects were also unknown. The aim of our study was to explore whether the pre-pregnancy exposure of hair dye and irregular menstruation were associated with the risk of abnormal birth weight. Methods We conducted a nested case-control study from a prospective cohort of 6203 pregnant women. Low birth weight study included 315 mother-infant pairs (105 LBW cases and 210 matched controls), and macrosomia study included 381 mother-infant pairs (127 macrosomia cases and 254 matched controls). Meanwhile, lifestyle information including hair dying custom and menstrual history were collected by face-to-face questionnaires and birth outcomes were extracted from the medical records. The logistic regressions models were used to analyze the join effect of irregular menstruation and hair dye use. Results Pre-pregnancy hair dye use was associated with increased risk of LBW (adjusted OR = 1.71, 95% CI: 1.01-2.92, P = 0.048). Irregular menstruation had high risk of LBW (adjusted OR = 2.79, 95% CI: 1.53-5.09, P = 0.001) and macrosomia (adjusted OR = 1.93, 95% CI: 1.09-3.44, P = 0.023). Additionally, in the LBW study, women who used hair dye with pre-pregnancy BMI < 18.5 kg/m2 had higher OR than those with only one risk factor (3.07 vs 2.53, P trend = 0.015), and women with both hair dye use and irregular menstruation also had higher risk than those with only one factor (4.53 vs 2.07, P trend = 0.05). Moreover, in macrosomia study, women with irregular menstruation and pre-pregnancy BMI ≥ 24 kg/m2 had higher risk than those with one factor (13.31 vs 2.09, P trend = 0.001). Conclusion Our study showed that either pre-pregnancy hair dye use or irregular menstruation was associated with abnormal birth weight, especially, their joint effects could furthermore increase the risk of low birth weight infants when these two factors existed simultaneously.